Processing of a cowpea - Groundnut blend into a miso-like product - Tano-Debrah, K.; Gbeddy, D.V. (International Journal of Food Sciences and Nutrition, 2004)
A traditional salt-miso process was used to produce a miso-like product from a 50-50 mixture of cowpea and groundnuts in a 60-day fermentation process as part of a study to determine the suitability of local legumes as raw materials for the production of miso. The koji was freshly prepared from a locally obtained rice and Aspergillus oryzae spores obtained from Japan. An old miso sample also obtained from Japan was used as the source of lactic acid bacteria. The physico-chemical changes in the product associated with the fermentation and the functional and quality characteristics of the final product were determined. The study demonstrated the possibility of processing the legume blend into a miso-like product. The physico-chemical, functional and quality characteristics of the final product showed the suitability of the product for its intended use as a soup base. The product had a high protein and a moderately high lipid content (about 25% and 29%, respectively), which could contribute to the nutritional contents of diets. © 2004 Taylor & Francis Ltd.
Keywords: Cowpea; Groundnut blend; Miso-like product; Aspergillus oryzae